Conducting polymer as potential retrofitting material for gas diffusion electrode to enhance microbial electrosynthesis: State-of-the-art review - Balachandran K.; Yeo R.Y.Z.; Abu Bakar M.H.; Ang W.L.; Salehmin M.N.I.; Fontmorin J.-M.; Lim S.S. (Elsevier Ltd, 2025)
Microbial electrosynthesis (MES) have been proven effective at reducing carbon dioxide (CO2) and synthesizing valuable organic commodities with the aid of electrical energy. The development of highly productive MES is challenging due to low bacterial loading, low electron transfer rate, and low solubility of CO2, which can decrease the production of relevant chemicals and further limit the future potential of upscaling. Many innovations have been established to upscale the system including the application of gas diffusion electrodes (GDEs) in a three-chambered MES system. To date, two types of commercially available GDEs have been employed in MES: polytetrafluoroethylene (PTFE) and carbon-based GDEs. The process of bacterial adhesion on the electrolyte-facing side of the GDE is influenced by material surface properties, such as surface charge, wettability, roughness, and area. Thus, a suitable material is required to modify the aforementioned GDE surfaces. Recently, researchers have been keen on modifying bio-electrodes with conducting polymers in microbial fuel cells and MES as they show fascinating outcomes. Moreover, modifying GDEs using conducting polymers (CPs) is well-established in fuel cells but highly lacking in MES. Several modification strategies can be adopted in MES, such as the microporous layer (MPL) coating, CP MPL, and CP-based MPL. Last, the present review features possible modifications of carbon-based GDE using CPs and its challenges. ? 2023 Hydrogen Energy Publications LLC